2020
DOI: 10.18844/wjet.v12i4.5190
|View full text |Cite
|
Sign up to set email alerts
|

Determination of primary school children’s speech skills in interdisciplinary communication in learning environments

Abstract: This aims to determine the formation of primary school children’s speech skills in interdisciplinary communication in learning environments in learning environments and verify the effectiveness of a methodology for the improvement of speech skills in interdisciplinary communication in learning environments in learning environments. The theoretical significance of the study allows clarifying knowledge on the issue of the formation of speech skills; practical significance lies in the presentation and testing of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 17 publications
0
12
0
1
Order By: Relevance
“…In the educational activities, younger students are most attracted to the emotionality, external entertainment of the lesson, game moments in it, and to a much lesser extent the cognitive side (Yesnazar et al, 2020). However, in Davydov's research, it was found that in experimental training, when the child's attention is drawn to the origin, meaning and essence of phenomena, the cognitive component appears more clearly.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the educational activities, younger students are most attracted to the emotionality, external entertainment of the lesson, game moments in it, and to a much lesser extent the cognitive side (Yesnazar et al, 2020). However, in Davydov's research, it was found that in experimental training, when the child's attention is drawn to the origin, meaning and essence of phenomena, the cognitive component appears more clearly.…”
Section: Introductionmentioning
confidence: 99%
“…The development of human communication capabilities in modern society is becoming an extremely urgent problem (Yesnazar et al, 2020). The improvement of scientific technologies has led to an increase in the needs of society for people who could set and solve problems related not only to the present, but also to the future.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research in the field mostly covers the educational use of museums. While creative drama practices in museums are still a new research area, creative drama practices in virtual museums are an area that has become widespread in recent years and where extremely limited research has been conducted (Yesnazar et al, 2020). Research findings and studies in the field reveal that teachers do not have full competence in this field, but they are warmly interested in creative drama applications in the virtual museum in education .…”
Section: Discussionmentioning
confidence: 99%
“…It is important to consider how language can achieve the desired value and to address the question of what role the education system can play in this (Yesnazar et al, 2020). In countries that have gone through or are going through a similar process, various applications have been brought up to enable families to decide on which language their children will receive education in.…”
Section: Introductionmentioning
confidence: 99%